The Role of Female Coach Leadership on Martial Arts Athlete Achievements - B Berliana; Ira Purnamasari; Mona Fiametta Febrianty; Dede Rohmat Nurjaya (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2021)
The purpose of this study was to reveal the success of female coaches in training elite sports. The method used was descriptive. The questionnaire was distributed to male and female athletes whom female coaches trained. The population involved in this study were eight female martial arts coaches (aged 25 to 45 years with training experience ranging from 5 to 15 years) and 72 martial arts athletes (35 male, 37 female) aged 15 to 40 years. The sport that was deliberately chosen was the martial arts sport. Martial art sport was chosen as female coaches in martial arts sports were still relatively few. The study results reported that there was a significant relationship between the leadership of female coaches and the performance of Judo athletes. Meanwhile, for Tae Kwondo, Tarung Derajat, Boxing, and Fencing sports, there was an insignificant relationship between female coach leadership and athlete achievement. Therefore, it is suggested to provide opportunities for female coaches to train martial arts sports.